Demographic and Surgical Profile of the Patients Underwent Minimally Invasive Cardiac Surgery in a Rural Center of Bangladesh (KYAMC Journal, 2021)
Background: Ever Since its inception , minimally invasive cardiac surgery is growing rapidly for better convenience and superb post operative outcome. As newer instruments, surgical technique and operative exposure are increasing more and more patients are demanding minimally invasive cardiac surgery.Objective: The study was conducted to evaluate the various pre operative and peroperative factors in minimally invasive cardiac surgery.Materials and Methods: A retrospective observational study on the patients who underwent minimally invasive cardiac surgery in the department of cardiovascular and thoracic surgery, Khwaja Yunus Ali Medical College, Sirajganj, Bangladesh from January 2016 to December 2020.Results: A total of 40 cases were operated through minimally invasive cardiac surgery in our department. Maximum number of cases was Atrial septal defect(ASD), and minimally invasive direct coronary artery bypass (MIDCAB). About 62.50% were female, majority of patients were in the range of 11-15 years. Right anterolateral thoracotomy was done in 27 cases and left anterolateral thoracotomy in 10 cases. The maximum number of cannulation done in femoral artery and femoral vein, followed by direct superior vena caval cannulation and only a single percutaneous superior venacaval cannulation through internal jugular vein. In 14 cases the length of incision was in the range of 3-4 cm and 12 cases in 4-5cm.Conclusion: Minimally invasive cardiac surgery is now becoming more demanding. As more and more centers are opening the door to newer technology, common people are also becoming conscious about its excellent post operative outcome.KYAMC Journal.2021;12(02): 71-74